Pengembangan Website Pembelajaran Online Berbasis CMS JCOW Sebagai Media Pembelajaran Sejarah - Alim, Muhammad Rofiul (Inovasi: Jurnal Diklat Keagamaan, 2023)
The utilization of technology in the world of education is an innovation and is considered to provide new experiences. One of the technology-based learning media is an online learning website. Creating an online learning website for history learning as an innovation in accessibility media learning. This type of study uses research and development (R&D) methods. The subject of the test is history education students. Data collection and analysis uses a questionnaire with qualitative and quantitative data types. The results of questionnaires from 20 respondents showed that online learning websites are useful. The use of online learning websites in one week is quite frequent which requires an online learning websites. Based on research carried out in small and large classes, the following conclusions were obtained. First, online learning websites are a relatively new innovation for history learning. In general, online learning websites are general and not specific to history learning. Second, proper hosting and domain provide maximum view when using an online learning website. Hosting and domain in premium category provide access for learning websites with velocity access, server disruptions, website hacking and backup are overcome. The result of media and material validation obtained very feasible result, while the small and large class trials also obtained very decent results.